A water-soluble and highly specific fluorescent probe for imaging thiophenols in living cells and zebrafish. (10th April 2019) - Li, Zilu; Liu, Caiyun; Yu, Chen; Yuan, Ruifang; Jia, Pan; Wang, Zuokai; Duan, Qingxia; Zhu, Hanchuang; Zhu, Baocun; Sheng, Wenlong
Abstract : A water-soluble and highly specific fluorescent probe was developed to track thiophenols in living cells and zebrafish. Abstract : A water-soluble fluorescent probe for monitoring thiophenols based on a GFP-type TPC-OH fluorophore and a 2, 4-dinitrophenyl ether recognition unit was designed. This probe possessed remarkable sensitivity and specificity toward thiophenols in an almost pure aqueous solution, and also showed good interference immunity to other related analytes including aliphatic mercaptans. Meanwhile, the probe displayed a prominent linear correlation between the thiophenol concentrations in the range of 0 to 20 μM and the fluorescence intensities at 492 nm, and the detection limit was as low as 33 nM. More strikingly, probe 1 was employed to visualize thiophenol in both living cells and zebrafish, which further demonstrated that probe 1 was a powerful practical tool in monitoring thiophenols in living systems.